Factores que explican las conductas inadecuadas respecto al mal manejo de la basura por los moradores del barrio San cayetano bajo de la ciudad de Loja. - Severino Correa, Carmelina Esperanza. (2014)
The type of study is descriptive, cuali-quantitative; it stops to establish the degree of participation communitarian in the disposition of the sweepings, for the study considered a universe of 150 families, from who a sample of 108 families was taken. In the present investigation the objective general was to identify the factors major for the inhabitants of the neighborhood San Cayetano made under poor management of waste , considering their condition sociocultural and objectives specific were: to determine the degree of community participation in the provision garbage , whether the existence of vacant lots acts as an incentive for poor garbage disposal , whether the absence of collectors front loading is affecting inadequate garbage collection, determine whether the service offering garbage collection agrees with the demands of the population. The technique used was the key informant interview and survey of heads of household. The results obtained were: 54% represented by heads of households and 46% of heads of household, in the knowledge of municipal regulations intradomiciliary waste management knows 69% compared to 31 % the unknown. When asked if the mismanagement of waste cause health problems 95 % are aware that if and 5% unknown waste management. Residents of the neighborhood presented as main activity of traders by 34 %, private employee by 19% and the remaining percentage is shared by public employee, farmer and others. With regard to the conclusions we have that the absence of collectors front loading affects inadequate garbage collection; the degree of community participation is poor due to lack of commitment to the inhabitants of this district regarding the disposal of waste. Keywords : involvement community, management waste, regulations municipal